2001
DOI: 10.1046/j.1523-1755.2001.59780144.x
|View full text |Cite
|
Sign up to set email alerts
|

A modified dialyzer with vitamin E and antioxidant defense parameters

Abstract: The results of our study suggest that the modified dialyzer with vitamin E provided more effective antioxidant defense than peroral administration of vitamin E in our hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Similar protection of neutrophil function was observed with the vitamin E dialyzer by Omata et al [44]. Mydlik et al [45] found that the vitamin E dialyzer decreased plasma MDA levels.…”
Section: Vitamin-e-coated Dialyzer: Potential Benefitssupporting
confidence: 68%
“…Similar protection of neutrophil function was observed with the vitamin E dialyzer by Omata et al [44]. Mydlik et al [45] found that the vitamin E dialyzer decreased plasma MDA levels.…”
Section: Vitamin-e-coated Dialyzer: Potential Benefitssupporting
confidence: 68%
“…Changes in plasma and RBC glutathione peroxidase (GSH-PX) activities were reported in 3 [11,26,44] and 5 studies [36,44,49,55,58] , respectively. Data on RBC superoxide dismutase (SOD) activity were available in 5 studies [11,26,49,55,58] .…”
Section: Outcome Datamentioning
confidence: 99%
“…To address this issue, several groups recently focused on developing hemodialysis membranes with antioxidative properties. The most commonly used approach is to immobilize antioxidants, such as vitamin E [1][2][3], linoleic acid [4][5][6][7], soybean-derived phytochemical, genistein [8] and alpha lipoic acid [9], on surfaces of the membranes that are in contact with blood. Antioxidant immobilization did not only allow for the inhibition of reactive oxygen species (ROS) generation but also reduced platelet adhesion and protein adsorption and prolonged blood coagulation time [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%